2013
DOI: 10.1073/pnas.1304923110
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity landscape of pyruvate under simulated hydrothermal vent conditions

Abstract: Pyruvate is an important "hub" metabolite that is a precursor for amino acids, sugars, cofactors, and lipids in extant metabolic networks. Pyruvate has been produced under simulated hydrothermal vent conditions from alkyl thiols and carbon monoxide in the presence of transition metal sulfides at 250°C [Cody GD et al. (2000) Science 289(5483):1337-1340], so it is plausible that pyruvate was formed in hydrothermal systems on the early earth. We report here that pyruvate reacts readily in the presence of transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…Iron sulfides have also been shown to be capable of driving reductive amination of α-keto acids to form amino acids (31,32). However, Huber and Wächtershäuser (32) found that amino acid synthesis did not occur with freshly precipitated sulfides of other metals including Zn, Mn, Co, Cu, and Ni and that replacing the Fe(II) with Ni(II) in sulfide precipitates simply decreased the amino acid yield proportional to the decreased concentration of Fe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron sulfides have also been shown to be capable of driving reductive amination of α-keto acids to form amino acids (31,32). However, Huber and Wächtershäuser (32) found that amino acid synthesis did not occur with freshly precipitated sulfides of other metals including Zn, Mn, Co, Cu, and Ni and that replacing the Fe(II) with Ni(II) in sulfide precipitates simply decreased the amino acid yield proportional to the decreased concentration of Fe.…”
Section: Resultsmentioning
confidence: 99%
“…presence of sulfide), and the amino acid alanine (in the presence of ammonia) (31)(32)(33). Novikov and Copley (31) showed that, even when ammonia was present, the yield of alanine synthesis from pyruvate (and whether alanine formed at all in favor of some other product) was dependent on which mineral was present.…”
mentioning
confidence: 99%
“…For the second scenario, serpentinization reactions have been demonstrated both in the lab and the field to promote abiotic synthesis of diverse complex organic compounds including hydrocarbons, carboxylic acids, amino acids, etc. by the reduction of inorganic precursors (Huber & Wächtershäuser, 1998, Proskurowski et al, 2008, Novikov & Copley, 2013. Recently, in-situ 4 evidence of abiotically formed tryptophan was obtained at depth beneath the Atlantis Massif (Mid-Atlantic Ridge), suggesting that the serpentinizing hydrothermal field could synthesize some prebiotic molecules of interest efficiently (Ménez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, methanethiol is the presumptive abiotic precursor of acetyl thioester (8,12,13)-the functional moiety of the Acetyl-CoA coenzyme central to many ancient metabolic pathways-and a sustainable abiotic source of acetyl thioesters is a key feature of models proposing the emergence of primordial metabolism in hydrothermal settings (5). Alkyl thiols are additionally implicated in the synthesis of the key metabolite pyruvate (10), which is speculated to have led to a primordial protometabolic network in a hydrothermal setting (14). In modern hot spring environments, hydrothermally produced thiols could constitute metabolic energy and carbon sources (15) for mesophilic and thermophilic microorganisms in subseafloor, near-vent, and plume settings given that such compounds are intensively cycled in sedimentary microbial habitats (16).…”
mentioning
confidence: 99%